Atomic Ensemble Effects and Non-Covalent Interactions at the Electrode–Electrolyte Interface - Cuesta, Angel (Makara Journal of Science, 2016)
Cyanide-modified Pt(111) electrodes have been recently employed to study atomic ensemble effects in electrocatalysis. This work, which will be briefly reviewed, reveals that the smallest site required for methanol dehydrogenation and formic acid dehydration is composed of three contiguous Pt atoms. By blocking these trigonal sites, the specific adsorption of anions, such as sulfate and phosphate, can be inhibited, thus increasing the rate of oxygen reduction reaction by one order of magnitude or more. Moreover, alkali metal cations affect hydrogen adsorption on cyanide-modified Pt(111). This effect is attributed to the non-covalent interactions at the electrical double layer between specifically adsorbed anions or dipoles and the alkali metal cations. A systematic investigation is conducted on the effect of the concentration of alkali metal cations. Accordingly, a simple model that reproduces the experimental observations accurately and enables the understanding of the trends in the strength of the interaction between M+ and CNad when moving from Li+ to Cs+, as well as the deviations from the expected trends, is developed. This simple model can also explain the occurrence of super-Nernstian shifts of the equilibrium potential of interfacial proton-coupled electron transfers. Therefore, the model can be generally applied to explain quantitatively the effect of cations on the properties of the electrical double layer. The recently reported effects of alkali metal cations on several electrocatalytic reactions must be mediated by the interaction between these cations and chemisorbed species. As these interactions seem to be adequately and quantitatively described by our model, we expect the model to also be useful to describe, explain, and potentially exploit these effects.